Numerical Study on the Influence of the Plasma Properties on the Keyhole Geometry in Laser Beam Welding - Coviello, Donato; D’Angola, Antonio; Sorgente, Donato (Frontiers in Physics, 2022)
Keyhole laser welding is the benchmark for deep-penetration joining processes. It needs high incident laser beam power densities at the workpiece surface to take place. Gaseous phase plays a fundamental role to keep the deep and narrow keyhole cavity open during the process. The plasma created in this process is a mixture of ionized metal vapors and the environmental gas and it develops inside the keyhole (keyhole plasma) and above the workpiece surface (plasma plume). The presence of plasma implicates absorption, scattering and refraction of laser beam rays. These phenomena alter the power density of the laser beam irradiating the workpiece surface and thus affect the resulting welding process. In this work, a mathematical and numerical model has been developed to calculate the keyhole shape taking into account the plasma absorption effects. The model considers the keyhole walls as the liquid-vapor interface and computes the keyhole geometry applying a local energy balance at this interface. In addition, the model takes into account the multiple reflections effects inside the cavity through an iterative ray-tracing technique, and it calculates the absorption mechanism due to inverse Bremsstrahlung for each ray along its segmented path inside the keyhole. Results show the effect of plasma properties on the keyhole shape and depth.